ROBUST CONTROL OF ADAPTIVE SINGLE INPUT FUZZY LOGIC CONTROLLER FOR UNMANNED UNDERWATER VEHICLE - Mohd Aras, Mohd Shahrieel; Mohd Shah, Hairol Nizam; Ab Rashid, Mohd Zamzuri (Little Lion Scientific Islamabad Pakistan, 2013)
In this paper the investigation of Adaptive Single Input Fuzzy Logic Controller (ASIFLC) as robust control of an Unmanned Underwater Vehicle (UUV). Robust control methods are designed to function properly with a present of uncertain parameters or disturbances. Robust control methods aim to achieve robust performance and stability in the presence of bounded modeling errors. The UUV applied in this research is a Remotely Operated Vehicle (ROV). Three ROV model will be used to apply ASIFLC such as ROV model was developed by UTeRG Group, ROV Model “Mako” was developed by Louis Andrew Gonzalez and RRC ROV- unperturbed with 6 DOF was developed by C.S. Chin. The simulation of controlling ROV by ASIFLC focused on depth control (heave motion). The ASIFLC for depth control of the ROV was successfully tested in simulation and real time by UTeRG Group. The simulation uses MATLAB Simulink and the performances of system response for depth control of Adaptive Single Input Fuzzy Logic Controller for Unmanned Underwater Vehicle will be discussed. It is proved the Adaptive Single Input Fuzzy Logic Controller is the robust control for different model of the ROV.